Complete remission of metastatic melanoma upon BRAF inhibitor treatment – what happens after discontinuation?. Issue 4 (August 2015) - Tolk, Henrike; Satzger, Imke; Mohr, Peter; Zimmer, Lisa; Weide, Benjamin; Schäd, Susanne; Gutzmer, Ralf
<x xml:space="preserve">Abstract</x> Treatment with BRAF inhibitors (BRAFi) leads to complete remissions (CR) in 3–6% of patients with BRAF mutant metastatic melanoma. In cases of CR, it is unclear whether BRAFi therapy should be continued. We retrospectively analyzed the clinical course of patients with metastatic melanoma who discontinued BRAFi therapy after achieving a CR. In 12 patients, CR of metastatic melanoma was diagnosed after a median BRAFi treatment duration of 13 (range 0.3–32) months. Reasons for discontinuation were side effects in seven patients and patient demand in five patients. Six patients are still in CR after a median of 17 (range 2–26) months after discontinuation of BRAF inhibition. Six patients developed a melanoma recurrence after a median of 3 (range 2–17) months of discontinuation of BRAFi therapy. Subsequently, these patients were again treated with a BRAFi, which resulted in three CR, one stable disease, and one progressive disease; one patient could not be assessed. Melanoma patients achieving CR during BRAFi therapy represent a heterogeneous group. Discontinuation of BRAFi therapy after a CR has to be balanced carefully with the potential risk of nonresponding to BRAFi retreatment in the case of relapse.